Epidermoid cyst of the renal pelvis masquerading as malignancy - Dinesh Pradhan; Gabriela Quiroga-Garza; Ronald Hrebinko; Rajiv Dhir; Anil V Parwani (Wolters Kluwer Medknow Publications, 2017)
Epidermoid cyst of the renal pelvis is exceptionally rare. The histogenetic mechanism has not been well characterized. Herein, we report a case of intrarenal epidermoid cyst in a 62-year-old woman who had undergone left nephrolithotomy for a staghorn calculus. She was being followed up for bilateral renal cysts when a complex mass was noted arising from the lower pole of the left kidney. Renal ultrasound showed a small left kidney with a solid vascular echogenic mass. A laparoscopic radical nephrectomy was performed. Gross examination revealed a well-circumscribed cystic mass with friable tan-yellow contents. Microscopically, a cystic structure lined by mature epidermis without atypia indicating epidermoid cyst was noted. The lesion appeared to be in continuity with the pelvicalyceal urothelium which displayed extensive squamous metaplasia. The patient is disease free and is doing well. Better clinical awareness of this benign entity and a preoperative biopsy may help preserve a kidney.